MANAJEMEN KESISWAAN JARINGAN SEKOLAH ISLAM TERPADU DI SMP IT INSAN MANDIRI KOTA SUKABUMI DALAM MEMBINA KEPRIBADIAN ISLAMI - Saepul Anwar; Tatang Hidayat; Mulyawan Sofwandi (STIT PRINGSEWU, 2023)
Abstract The purpose of this study was to analyze the student management of an integrated Islamic school network at SMP IT Insan Mandiri Sukabumi City. This research uses a qualitative approach and a descriptive method. Data collection techniques with interviews, observations and documentation studies. Based on the results of the study, the concept of student management is divided into four parts, namely planning, organizing, implementing and evaluating. In planning, all planning is prepared by the vice principal for student affairs assisted by student staff and for its organization is appointed by the Principal of the teachers at SMP IT Insan Mandiri as the implementer in running the organization. The implementation of student management activities is mentored by the persons in charge, namely from among the teachers and the object is all students who are included in the development of extracurricular and intracurricular activities. The implementation of special guidance and training to strengthen the skills and interests of students' talents in the evaluation of student activities is then implemented through activities resulting from the development of student interests and skills in extracurricular activities and their participation in every competition activity carried out both at the provincial and national levels.